Risk Evaluation Method of Import and Export Goods Based on Fuzzy Reasoning and DeepFM. (12th June 2021) - Xu, Yuanyuan; Fang, Huijuan; Luo, Jiliang; He, Jianan; Li, Tao; Lin, Shiming
Abstract : At present, the inspection mode of China's import ports is generally manual based on experience, or random inspection by the document review system according to a preset random inspection ratio. In order to improve the detection rate of unqualified goods and realize the best allocation of limited human and material resources of inspection and quarantine institutions, a method composed of fuzzy reasoning, deep neural network, and factorization machine (DeepFM) was proposed for the intelligent evaluation of risk sources of imported goods. Fuzzy reasoning is used to realize the fuzzy normalization of the dataset samples, the DeepFM deep neural network is finally used for training and learning to classify and evaluate the risks of goods. Results of experimental tests on a specific customs import and export dataset verify the effectiveness of the proposed research method.